Quality of mentoring of mentor teachers: Perspective of the trainee teachers - Mohd Fairuz Jafar; Mohd Faiz Mohd Yaakob; Ramlan Mustapha; Muhammad Noor Abdul Aziz; Mat Rahimi Yusof; Hapini Awang (International Journal of Evaluation and Research in Education (IJERE), 2021)
Mentoring by the mentor teachers to the trainee teacher is an important element in the component of professional practice, namely practicum. Mentoring of mentor teachers in this study refers to the quality of guidance given by mentor teachers to trainee teachers. This aspect is seen to have an impact on the success of trainee teachers during the practicum session. However, there are past studies that state that mentor teachers do not provide guidance as required by the trainee teachers. Therefore, this study aimed to examine the quality of mentoring of mentor teachers from the perspective of trainee teachers. This study used a mixed-method approach. Quantitative study was using a questionnaire namely mentor teacher’s guidance while utilizing random sampling method was used on a sample of 217 trainee teachers from the Institute of Teacher Education in the northern zone of Malaysia who have undergone the practicum session. The qualitative approach, on the hand involve semi-structured interview with two trainee teachers as the participants. This study found that the quality of guidance of mentor teachers is at a very good level. Quantitative findings are supported by qualitative findings. Four themes were identified from the interview analysis namely; excellent guidance, informative, cooperation and the needs of mentor teachers.